Stand-up pouches with recycled polyethylene

By adopting a multi-layer polyethylene laminated structure in an upright pouch, combining HDPE, LLDPE, MDPE and recycled polyethylene, a two-layer sealant system is formed, which solves the problem of poor sealing of SUP on recycled materials and improves the packaging Recirculation capability and performance.

CN114364535BActive Publication Date: 2025-01-14NOVA CHEM (INT) SA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080065570.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-20
Filing Date
2020-09-14
Publication Date
2025-01-14
Estimated Expiration
2040-09-14

AI Technical Summary

Technical Problem

The existing upright pouches (SUPs) are difficult to recirculate on the construction material, and the effectiveness of the sealant layer is reduced when recirculating polyethylene (r.PE) is used.

Method used

A multi-layer polyethylene laminated structure is adopted, in which the outer web includes HDPE, LLDPE and MDPE, the inner web contains recirculated polyethylene, and the sealing effectiveness is improved through a two-layer sealant system, with the density of the sealant surface layer higher than the adjacent layer But lower than the core layer density.

Benefits of technology

Improves the sealing effectiveness and overall performance of SUP, enhances the recirculation ability and impact resistance of the packaging, and provides better optical properties and stiffness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114364535B_ABST
    Figure CN114364535B_ABST
Patent Text Reader

Abstract

In some embodiments, a stand-up pouch (SUP) is prepared using a polyethylene structure having a first web and a second web. The webs are laminated together to form a polyethylene structure for preparing the SUP. One web comprises a layer of recycled polyethylene (r.PE). In some cases, it has been observed that the use of r.PE reduces the effectiveness of the sealant layer of the overall structure. In some embodiments, the SUP disclosed herein has a two-layer sealant system to alleviate this problem.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present disclosure relates to a laminated structure prepared by laminating a first polyethylene web to a second polyethylene web. The laminated structure is suitable, for example, for preparing a stand-up pouch (SUP). The SUP is made of recycled polyethylene and is recyclable.

[0002] Stand up pouch ("SUP") packaging is widely used commercially as packaging for consumer goods. These pouches are attractive to consumers and, when properly designed, are very efficient using a minimum amount of polymer material to prepare the package.

[0003] SUP packaging was first produced more than 30 years ago. Early designs used a laminate of polyethylene terephthalate (PET) layers and polyethylene (PE) layers. The typical structure had a thin layer of PET (about 0.5 mil or 0.12 mm thick) and a thicker layer of PE (about 3 mil or 0.75 mm). This type of design is still used commercially.

[0004] The problem with this SUP design is that the pouch is difficult to recycle due to the different materials of construction.

[0005] It is known to prepare "recyclable" SUPs made only with polyethylene (or with at least 95% PE, as many recycling facilities are able to recycle coextruded or laminated films containing at least 95% PE as "pure" PE materials). For example, U.S. Patent Application Publication No. 2016 / 0229,157 (NOVA Chemicals) describes a SUP that contains at least 95% PE by weight and is therefore recyclable.

[0006] There is a further need for the use of recycled polyethylene ("r.PE") in new pouches. We have observed that including r.PE in SUPs can reduce the effectiveness of the sealant layer in the film structure used to make the SUP. We have now discovered that a two-layer sealant system alleviates this problem and provides enhanced sealing effectiveness. Summary of the invention

[0007] Disclosed herein is a laminate structure made of a polymer material, the laminate structure comprising:

[0008] A) External webs, including:

[0009] A.1) comprising a first A layer of a HDPE composition, and

[0010] A.2) a second A layer comprising a polyethylene selected from the group consisting of LLDPE, MDPE and HDPE;

[0011] B) Inner webs, including:

[0012] B.1) a first B layer in contact with the outer web, wherein the first B layer comprises a polyethylene selected from the group consisting of LLDPE and MDPE,

[0013] B.2) a second B layer comprising recycled polyethylene, and

[0014] B.3) Sealant structure, including:

[0015] B.3.1) sealant surface layer including polyethylene sealant, and

[0016] B.3.2) a layer adjacent to the sealant skin layer, the layer comprising polyethylene having a density a) higher than the density of the polyethylene sealant and b) lower than the density of the core layer in contact with the layer adjacent to the sealant skin layer; and

[0017] in

[0018] I) the outer web is laminated to the inner web, and

[0019] II) said HDPE, MDPE, LLDPE, recycled polyethylene and polyethylene sealant together form at least 95% by weight of said polymeric material used to prepare said laminate structure.

[0020] Disclosed herein is a laminate structure made of a polymer material, the laminate structure comprising:

[0021] A) External webs, including:

[0022] A.1) comprising a first A layer of a HDPE composition,

[0023] A.2) a second A layer comprising a polyethylene selected from the group consisting of LLDPE, MDPE and HDPE, and

[0024] A.3) a third A layer comprising a polyethylene selected from the group consisting of LLDPE, MDPE and HDPE;

[0025] B) Inner webs, including:

[0026] B.1) a first B layer in contact with the outer web, wherein the first B layer comprises a polyethylene selected from the group consisting of HDPE, LLDPE and MDPE,

[0027] B.2) a second B layer comprising recycled polyethylene, and

[0028] B.3) Sealant structure, including:

[0029] B.3.1) sealant surface layer including polyethylene sealant, and

[0030] B.3.2) a layer adjacent to the sealant skin layer, the layer comprising polyethylene having a density a) higher than the density of the polyethylene sealant and b) lower than the density of the core layer in contact with the layer adjacent to the sealant skin layer; and

[0031] in

[0032] I) the outer web and the inner web each optionally comprise at least one additional polyethylene layer between A.1 and A.3 and B.1 and B.3,

[0033] II) the outer web is laminated to the inner web, and

[0034] III) said HDPE, MDPE, LLDPE, recycled polyethylene and polyethylene sealant together form at least 95% by weight of said polymeric material used to prepare said laminate structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 and 2 The properties of seals made using different inner webs are shown. DETAILED DESCRIPTION

[0036] In one embodiment, the polymeric material used to make the SUP comprises different types of polyethylene. In one embodiment, the polymeric material used to prepare the SUP consists essentially of different types of polyethylene, i.e., the only polymeric material used to prepare the SUP of this embodiment is polyethylene. The term polyethylene refers to a polymer comprising ethylene and may comprise optional comonomers.

[0037] Suitable examples of polyethylene include:

[0038] 1) High-density polyethylene (HDPE) - a polyethylene homopolymer or copolymer having a density of about 0.95 to about 0.97 g / cc;

[0039] 2) Medium density polyethylene (MDPE) - a polyethylene copolymer having a density of about 0.93 to about 0.95 g / cc;

[0040] 3) Linear low density polyethylene (LLDPE) - a polyethylene copolymer having a density of about 0.915 to about 0.93 g / cc; and

[0041] 4) Polyethylene sealant - a polyethylene material suitable for making thermoformed seals, or, for example, a polyethylene selected from the following: 1) a polyethylene copolymer having a density of about 0.88 to 0.915 g / cc ("VLDPE"); and 2) High Pressure Low Density Polyethylene (LD) - a polyethylene homopolymer made in a high pressure process with a free radical initiator having a density of about 0.91 to about 0.93 g / cc.

[0042] In some embodiments, only the outer web comprises a HDPE layer. In another embodiment, both the inner and outer webs of the laminate structure include HDPE in at least one layer. The HDPE layer provides rigidity / rigidity to the SUP. In one embodiment, these HDPE layers are separated by at least one layer of lower density polyethylene (e.g., LLDPE), and this lower density polyethylene provides impact resistance and puncture resistance. In addition, by separating the rigid HDPE layers, the overall rigidity and torsional strength of the SUP are improved compared to a structure containing an equivalent amount / thickness of HDPE in a single layer, in a manner that can be referred to as an "I beam" effect (similar to the I-beams widely used in the construction of buildings).

[0043] The "adjacent" layer is in contact with the sealant skin layer on one side and with the core layer on the other side of the adjacent layer. The adjacent layer comprises a polyethylene composition having a density higher than that of the sealant skin layer but lower than that of the core layer which it also contacts. In one embodiment, the polyethylene composition is a blend of polyethylenes, in another embodiment it comprises a single type of polyethylene.

[0044] In embodiments where the outer and inner webs optionally comprise at least one additional polyethylene layer between A.1 and A.3 and B.1 and B.3, the additional layer comprises a polyethylene composition comprising HDPE, MDPE, LLDPE or a combination thereof. In further embodiments, these layers consist of HDPE, MDPE, LLDPE or a combination thereof. In further embodiments, these layers comprise recycled polyethylene. In further embodiments, these layers consist of recycled polyethylene.

[0045] Those skilled in the art will appreciate that when a blown multilayer film is produced on a multilayer line apparatus, each layer can be produced by a single line, or a "layer" can be produced by multiple continuous lines that produce layers of the same composition in successive layers. As an example, a five-layer line can produce a structure of composition A / B / C / D / E, producing a 5-layer film. Alternatively, the same five-layer line can be used to produce a 5-layer film of the composition A / A / B / C / C, effectively producing a three-layer film.

[0046] In some embodiments, the laminate structures of the present disclosure are suitable for preparing stand-up pouches (SUPs).

[0047] SUP packages are well known. They are typically prepared from "rollstock" (ie, a film or laminate structure as disclosed herein) using a variety of well-known techniques and machines.

[0048] SUPs are manufactured in many sizes and are typically used to package small quantities (e.g., from about 25 mils (ml) to 2 liters) of consumer products. The contents of a SUP package are often described as "flowable," where the term "flowable" is intended to include: particulate solids (e.g., candies, nuts, and breakfast cereals); liquids (e.g., beverages); and pastes / emulsions / sauces (e.g., yogurt and baby food). In one embodiment, the SUP is designed to allow the contents of an opened package to easily flow from the SUP (and / or be consumed directly). For example, the top of the SUP may be equipped with an integrated straw (for beverages) or a spout for pastes, emulsions, sauces, etc. Such designs are well known, and an example is disclosed in Canadian Patent Application Serial No. 2,612,940 (Rogers).

[0049] In some embodiments, the SUP is typically opened at the top of the package. The SUP may be opened with a tear strip, or a fitment (or lid) that allows the package to be reclosed, or other lids / closures known to those skilled in the art.

[0050] In one embodiment, the laminate structure is printed at the interface between the two webs, ie, on the inner surface of the first web or on the outer surface of the second web.

[0051] Detailed descriptions of various embodiments of the first (outer) web, various embodiments of the second (inner) web, various embodiments of the adhesive, and various embodiments of printing follow.

[0052] In one embodiment, the first (outer) web forms the outer wall of the laminate structure.

[0053] In one embodiment, the laminate structure is printed at the interface between the first web and the second (inner) web.

[0054] Because people "see through" the outer web to see the printing, in some embodiments, it may be desirable for the outer web to have a low haze value. In addition, in some embodiments, a high "gloss" may be desired because many consumers regard a high gloss finish as an indication of high quality.

[0055] Furthermore, in some embodiments, it is desirable for the outer layer to provide stiffness / rigidity to the laminate structure so that a SUP made from the laminate structure will be self-supporting.

[0056] Thus, the outer web may require a balance of good optical properties and stiffness. HDPE is known to provide the required stiffness, but it is also known that HDPE may have poor optical properties. Thus, in one embodiment, a very thin layer of HDPE is used as a skin layer in the outer web together with a lower density polyethylene layer.

[0057] Further description of these embodiments follows.

[0058] Multi-layer outer web or web A

[0059] Typically, using a thick single layer of HDPE film to form the outer web of a SUP can be used to provide a structure with sufficient rigidity. However, the thick HDPE layer may suffer from poor optical properties. This can be solved by printing the outer (face) side of the outer web to form an opaque SUP. However, this design may not be very resistant to abuse because the printing may be easily worn and damaged during transportation and handling of the SUP.

[0060] In one embodiment, the structure disclosed herein alleviates these problems by providing a coextruded multilayer film for the outer web in which at least one layer ("Layer A.1") is made of HDPE and at least one layer ("Layer A.2") is made of a lower density polyethylene (e.g., LLDPE, LD or VLDPE).

[0061] In one embodiment, the HDPE is further characterized by a melt index I 2 0.1-10 (or for example 0.3-3) g / 10 minutes.

[0062] In one embodiment, the first A layer is a HDPE composition that includes a nucleating agent.

[0063] In one embodiment, the LLDPE is further characterized by a melt index I 2 0.1-5 (or for example 0.3-3) g / 10 minutes.

[0064] In one embodiment, the LLDPE is further characterized by being produced using a single site catalyst, such as a metallocene catalyst, and having a molecular weight distribution Mw / Mn (ie, weight average molecular weight divided by number average molecular weight) of about 2 to about 4. Such LLDPEs are generally referred to as sLLDPEs.

[0065] In one embodiment, the very low density polyethylene (VLDPE) is a polyethylene having a density of about 0.88 to 0.915 g / cc and a melt index I 2 About 0.5 to 10 g / cc of ethylene copolymer. All of the above materials are well known and commercially available.

[0066] Lower density polyethylene can improve the optics of the multilayer web. In one embodiment, the multilayer structure is a three-layer coextruded film of the A / B / A type, where A is LLDPE (e.g., single-site catalyzed LLDPE) and B is a HDPE composition. This type of film provides excellent optical properties, to the point in some embodiments where it is observed that some of these films have better optical properties than monolayer films made with the same LLDPE.

[0067] In another embodiment, the LLDPE used in web A is blended with a small amount (0.2-10 wt%) of LD polyethylene having a melt index I 2 It is 0.2-5, or for example 0.2-0.8. These LLDPEs and certain blends of LLDPE and LD have been observed to have superior optical properties and superior stiffness compared to LLDPE alone (particularly when the LLDPE is sLLDPE).

[0068] In some embodiments, it has been observed that using LD resins having a melt index of about 0.2 to 0.8 g / 10 min is effective for this purpose (those skilled in the art typically refer to such LD resins as "fractional melt LD").

[0069] In another embodiment, the LLDPE used in Web A is blended with a small amount (0.2-10 wt%) of HDPE resin and a nucleating agent.

[0070] As used herein, the term "nucleating agent" is intended to convey its conventional meaning to those skilled in the art of preparing nucleated polyolefin compositions, ie, an additive that changes the crystallization behavior of a polymer as the polymer melt cools.

[0071] Examples of conventional nucleating agents that are commercially available and widely used as polypropylene additives are dibenzylidene sorbitol esters (for example, marketed by Milliken Chemical under the trademark MILLAD ® 3988 and is marketed by Ciba Specialty Chemicals under the trademark IRGACLEAR ® products sold).

[0072] In some embodiments, the nucleating agent should be well dispersed in the polyethylene. In some embodiments, the amount of nucleating agent used is relatively small, 200-10,000 parts per million by weight (based on the weight of the polyethylene), so those skilled in the art will understand that care must be taken to ensure that the nucleating agent is well dispersed. In some embodiments, the nucleating agent is added to the polyethylene in a finely divided form (less than 50 microns, or, for example, less than 10 microns) to facilitate mixing.

[0073] Examples of nucleating agents that may be suitable for use include cyclic organic structures disclosed in U.S. Pat. No. 5,981,636 (and salts thereof, such as disodium bicyclo[2.2.1]heptenedicarboxylate); saturated forms of the structures disclosed in U.S. Pat. No. 5,981,636 (as disclosed in U.S. Pat. No. 6,465,551; Zhao et al., to Milliken); salts of certain cyclic dicarboxylic acids having a hexahydrophthalic acid structure (or "HHPA" structure) as disclosed in U.S. Pat. No. 6,599,971 (Dotson et al., to Milliken); phosphate esters, such as those disclosed in U.S. Pat. No. 5,342,868 and those sold by Asahi Denka Kogyo under the trade names NA-11 and NA-21, and metal salts of glycerol (or, for example, zinc glycerolate). The calcium salt, calcium 1,2-cyclohexanedicarboxylate (CAS Reg. No. 491589-22-1) generally provides good results for nucleation of HDPE. The above nucleating agents can be described as "organic" (in the sense that they contain carbon and hydrogen atoms), and this distinguishes them from inorganic additives such as talc and zinc oxide. Talc and zinc oxide are commonly added to polyethylene (to provide antiblocking and acid scavenging, respectively), and they do provide some limited nucleating functionality.

[0074] The above-mentioned "organic" nucleating agents may be better (but more expensive) nucleating agents than inorganic nucleating agents. In one embodiment, the amount of organic nucleating agent is 200 to 2000 parts per million (based on the total weight of polyethylene in the layer containing the nucleating agent).

[0075] In some embodiments, these LLDPE / HDPE / nucleating agent blends have also been found to provide superior optical properties and higher modulus (higher stiffness) than 100% LLDPE.

[0076] In another embodiment, the outer web is a three-layer coextruded film of type A / B / A, wherein A is HDPE and B is a lower density polyethylene, such as the above-mentioned LLDPE composition (including LLDPE composition blended with LD, and LLDPE composition blended with HD and a nucleating agent). These films provide good rigidity.

[0077] B. Inner web (with recycled polyethylene); also "B" web; also "sealant" web

[0078] The inner web forms the interior of a SUP made from a laminate structure.

[0079] B.1) a first B layer in contact with the outer web, wherein the first B layer comprises a polyethylene selected from the group consisting of HDPE, LLDPE and MDPE,

[0080] B.2) a second B layer comprising recycled polyethylene, and

[0081] B.3) Sealant structure, including:

[0082] B.3.1) sealant surface layer including polyethylene sealant, and

[0083] B.3.2) A layer adjacent to the sealant skin layer, the layer comprising polyethylene having a density a) higher than the density of the polyethylene sealant; and b) lower than the density of the core layer in contact with the layer adjacent to the sealant skin layer.

[0084] B.1 Interface surface

[0085] One surface layer of the inner web is made of a polyethylene composition having a density lower than that of HDPE, so as to provide a layer with enhanced impact and tear strength properties compared to a layer made of HDPE. In one embodiment, this layer is made primarily of LLDPE (including sLLDPE) having a melt index of 0.3-3 g / 10 min. This layer can also be made using a major amount of LLDPE (or sLLDPE) and a minor amount of LD (e.g., a split melt LD as described above) or a LLDPE+HDPE+nucleating agent blend as described above.

[0086] In another embodiment, the skin layer can be made of MDPE (or a blend of MDPE with a small amount of another polyethylene, such as LD, and blends with HDPE and the nucleating agents described above).

[0087] In one embodiment, the top layer is printed. Thus, any well-known modification of the film that facilitates the printing process is within the scope of the present disclosure. For example, the top layer may be subjected to corona treatment to improve ink adhesion. In another embodiment, the top layer may contain an opacifier (e.g., talc, titanium oxide, or zinc oxide) to improve the appearance of the printed surface.

[0088] B.2 Core layer including recycled polyethylene (r.PE)

[0089] The inner web comprises at least one layer comprising r.PE. The inner web comprises a core layer comprising r.PE. In one embodiment, the core layer consists essentially of r.PE (ie, all polymers used in the layer are r.PE).

[0090] There are many sources and types of recycled polyethylene that can be used in various embodiments disclosed herein. As used herein, the term recycled polyethylene (or r.PE) refers to recycled polyethylene independent of its source.

[0091] In one example, recycled polyethylene is any polyethylene that has been exposed to at least one "thermal history", i.e. it has been melted or molded or extruded at least once. In one embodiment, the r.PE may be post-industrial recycled (PIR), which generally refers to polyethylene that has been used in a manufacturing process but not sold to the end consumer (such PIR polyethylene is generally produced as scrap, trimmings or non-compliant parts in a manufacturing process - it is recovered for reuse in the same process, or it may be sold to other manufacturers / converters for use in a different process).

[0092] In one embodiment, r.PE is post-consumer recycled polyethylene (or "PCR"). PCR is recycled from the waste stream and cleaned before reuse.

[0093] In a specific embodiment, PCR is prepared from a recirculating container for liquid (eg, milk or juice).

[0094] r.PE density can be 0.910-0.97g / cc and melt index I 2 0.2-20.

[0095] In one embodiment, the density of r.PE is 0.93-0.95 g / cc and the melt index I 2 It is 0.2-10.

[0096] In other embodiments, the density is from 0.910 to 0.930, or from 0.930 to 0.950, or from 0.950 to 0.960.

[0097] B.3 Sealant structure - Sealant layer (B.3.1) and "adjacent" or "immediately adjacent" layer (B.3.2)

[0098] The inner web has two outer or "skin" layers, an interface skin layer (layer B.1, above) and an inner skin layer, also referred to herein as a sealant layer (B.3.1). The sealant layer is made of a "polyethylene sealant", i.e., a type of polyethylene that melts readily and forms a seal when subjected to sealing conditions. Those skilled in the art will recognize that two types of polyethylene are preferably used as sealants, namely: polyethylene copolymers having a density of about 0.88 to 0.915 g / cc; and LD polyethylene (as previously described).

[0099] In some embodiments, it is preferred to use lower density polyethylene copolymers. As a general rule, the cost of these lower density polyethylenes increases as the density decreases, so the "best" polyethylene sealant resin is usually the highest density polyethylene that provides satisfactory seal strength. Polyethylene sealants with a density of about 0.900 to 0.914 g / cc will provide satisfactory results for many applications.

[0100] Other examples of polyethylene sealants include ethylene vinyl acetate (EVA) and "ionomers" (e.g., copolymers of ethylene and an acidic comonomer, wherein the resulting acidic comonomer is neutralized, e.g., with sodium, zinc, or lithium; ionomers are marketed under the trademark SURLYN ® Commercially available).

[0101] The use of EVA and / or ionomers is less preferred as they may cause difficulties when the SUP is recycled (however, as previously noted, many recycling facilities will accept SUPs containing up to 5% EVA or ionomer for recycling).

[0102] B.3.2 “Immediately adjacent” or “adjacent” layers

[0103] We have observed that the use of r.PE in the inner web reduces the effectiveness of the sealant layer (compared to an inner web made with virgin HDPE instead of r.PE). The reasons for this are not fully understood. However, we have observed that the use of selected polyethylene in the layer in contact with (or "adjacent to") the sealant layer improves the sealing performance. To clarify: the sealant layer (described above) is the surface layer used to seal the SUP, and the "adjacent" layer is the core layer that is adjacent to / in contact with the sealant layer and is also in contact with another core layer. In one embodiment, the density of the "adjacent" layer is 0.917-0.921 g / cc. In some embodiments, B.3.2 The sealant layer (adjacent layer) may include recycled polyethylene alone or recycled polyethylene blended with virgin polyethylene. In these embodiments, the density of the selected polyethylene, recycled polyethylene, or blend of the two satisfies the following relative density, which allows the layer adjacent to the sealant surface layer to have a polyethylene whose density a) is higher than the density of the polyethylene sealant; and b) is lower than the density of the core layer in contact with the layer adjacent to the sealant surface layer.

[0104] In one embodiment, the density of rLLDPE is 0.927 g / cm 3 and with a density of 0.914 g / cm 3 VLDPE blends.

[0105] In one embodiment, the density of rLLDPE is 0.928 g / cm 3 and with a density of 0.912 g / cm 3 VLDPE blends.

[0106] B.5 HDPE

[0107] In one embodiment, the inner web further comprises at least a layer made from a HDPE composition, said layer optionally comprising a nucleating agent.

[0108] In one embodiment, the second B layer comprises a HDPE composition comprising a nucleating agent.

[0109] HDPE is a common commercial product. Most commercially available HDPE is produced from a catalyst comprising at least a metal such as chromium or a Group IV transition metal - Ti, Zr or Hf.

[0110] HDPE made with Cr catalysts typically contains some long chain branches (LCBs). HDPE made with Group IV metals typically contains less LCBs than HDPE made with Cr catalysts.

[0111] As used herein, the term HDPE refers to polyethylene (or a polyethylene blend as the context requires) having a density of about 0.95 to 0.97 grams per cubic centimeter (g / cc). In one embodiment, the melt index ("I 2 ”) is about 0.2 to 10 g / 10 minutes.

[0112] In one embodiment, the HDPE is provided as a blend composition comprising two HDPEs having melt indexes separated by a factor of at least 10. Further details of this HDPE blend composition are as follows.

[0113] HDPE blend composition

[0114] Blend ingredients

[0115] Blend ingredients a)

[0116] The blend component a) of the polyethylene composition used in this embodiment includes HDPE with a relatively high melt index. As used herein, the term "melt index" is intended to refer to the value obtained by ASTM D 1238 (when conducted at 190°C using a 2.16 kg weight). This term is also referred to herein as "I 2 ” (expressed as grams of polyethylene that flows in a 10 minute test time, or “g / 10 min”). As will be appreciated by those skilled in the art, the melt index I 2 Generally inversely proportional to molecular weight. In one embodiment, blend component a) has a relatively high melt index (or in other words, a relatively low molecular weight) compared to blend component b).

[0117] In these blends, the blend component a) I 2 The absolute value of I is usually greater than 5 g / 10 min. 2 The "relative value" of is more important and should usually be the I of blend component b). 2 Value [herein, I of blend component b) 2 The value is called I 2']. Therefore, for illustration purposes, if the blend component b) has an I 2 ' value is 1 g / 10 min, then the I 2 Values ​​are, for example, at least 10 g / 10 min.

[0118] In one embodiment, blend component a) may be further characterized by: i) a density of 0.95-0.97 g / cc; and ii) being present in an amount of 5-60 wt % of the total HDPE blend composition (with blend component b) forming the balance of the total composition), wherein the amount is 10-40 wt % or such as 20-40 wt %. It is permissible to use more than one high density polyethylene to form blend component a).

[0119] The molecular weight distribution is determined by dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn), where Mw and Mn are determined by gel permeation chromatography according to ASTM D 6474-99. The Mw / Mn of component a) is, for example, 2-20, or, for example, 2-4. While not wishing to be bound by theory, it is believed that for component a), low Mw / Mn values ​​(2-4) can improve the crystallization rate and overall barrier properties of blown film and web structures prepared according to the present disclosure.

[0120] Blend ingredient b)

[0121] Blend component b) is also a high density polyethylene having a density of 0.95-0.97 g / cc (eg, 0.955-0.968 g / cc).

[0122] The melt index of the blend component b) is also measured by ASTM D 1238 using a 2.16 kg load at 190°C. The melt index value of the blend component b) (referred to herein as I 2 ') has a lower melt index value than the blend component a), indicating that the molecular weight of the blend component b) is relatively higher. 2 The absolute value of ' is, for example, 0.1-2 g / 10 min.

[0123] The molecular weight distribution (Mw / Mn) of component b) is not critical to success, although a Mw / Mn of 2-4 is an example for component b).

[0124] Finally, the ratio of the melt index of component b) divided by the melt index of component a) is, for example, greater than 10 / 1.

[0125] The blend component b) may also comprise more than one HDPE resin.

[0126] Overall HDPE blend composition

[0127] The overall high density blend composition is formed by blending blend component a) and blend component b) together. In one embodiment, the overall HDPE composition has a melt index (ASTM D 1238, measured at 190°C with a 2.16 kg load) of 0.5-10 g / 10 min (eg, 0.8-8 g / 10 min).

[0128] The blends can be made by any blending process, such as: 1) physical blending of pelletized resins; 2) co-feeding different HDPE resins into a common extruder; 3) melt mixing (in any conventional polymer mixing equipment); 4) solution blending; or 5) a polymerization process using 2 or more reactors.

[0129] A suitable HDPE blend composition can be prepared by melt blending the following two blend components in an extruder: 10-30 wt % of component a), wherein component a) is a melt index I 2 HDPE resin having a melt index of 15-30 g / 10 min and a density of 0.95-0.97 g / cc; and 90-70 wt % of component b), wherein component b) is a melt index I 2 HDPE resin with a molecular weight of 0.8-2 g / 10 min and a density of 0.95-0.97 g / cc.

[0130] Examples of commercially available HDPE resins suitable for component a) are sold under the trademark SCLAIR ® It is sold as 79F, which is a HDPE resin made by homopolymerization of ethylene using a conventional Ziegler Natta catalyst. It has a typical melt index of 18 g / 10 min, a typical density of 0.963 g / cc, and a typical molecular weight distribution of about 2.7.

[0131] Examples of commercially available HDPE resins suitable for blend component b) include (typical melt index and density values ​​are shown in parentheses): SCLAIR ® 19G (melt index = 1.2 g / 10 min, density = 0.962 g / cc); MARFLEX ® 9659 (available from Chevron Phillips, melt index = 1 g / 10 min, density = 0.962 g / cc); and ALATHON ® L 5885 (available from Equistar, melt index = 0.9 g / 10 min, density = 0.958 g / cc).

[0132] In some embodiments, the HDPE blend composition is prepared by a solution polymerization process using two reactors operating at different polymerization conditions. This provides uniform, in-situ blending of the HDPE blend components. An example of this process is described in U.S. Pat. No. 7,737,220 (Swabey et al.).

[0133] In one embodiment, only ethylene homopolymers are used to prepare the HDPE composition. This type of composition is suitable if one wants to optimize (maximize) the barrier properties of the structure.

[0134] In another embodiment, copolymers may be used to prepare the HDPE composition, as this will achieve some improvement in physical properties, such as impact resistance. In yet another embodiment, a small amount (less than 30 wt%) of a lower density polyethylene may be blended into the HDPE composition (again, this may achieve some improvement in impact resistance).

[0135] In one embodiment, the HDPE blend composition described above is combined with an organic nucleating agent (as previously described) in an amount of about 300 to 3000 parts per million by weight, based on the weight of the HDPE blend composition. Using a calcium salt (previously described), 1-2 cyclohexanedicarboxylic acid calcium salt (CAS 491589-22-1) is suitable. In some embodiments, when the HDPE composition contains a nucleating agent, it is preferred to use a HDPE composition prepared with a Group IV transition metal (e.g., Ti).

[0136] Such "nucleated" core layers have been observed to provide excellent barrier properties (ie, reduced transmission of water, gas, and grease), which is desirable for many packaging applications.

[0137] In some embodiments, the presence of a nucleating agent has been observed to improve the modulus of the HDPE layer (compared to a non-nucleated layer of equivalent thickness).

[0138] Nucleated HDPE blend compositions using the type described above provide a "barrier" to oxygen and water transmission. The performance of this barrier layer is suitable for many commercial products. However, those skilled in the art will recognize that improved "barrier" properties can be achieved through the use of certain "barrier" polymers, such as ethylene vinyl alcohol (EVOH), ionomers and polyamides. The use of large amounts of such non-polyethylene barrier resins can make recycling of films / structures / SUPs made with a combination of polyethylene and non-polyethylene materials very difficult. However, if the amount of non-polyethylene material is low (less than 10 wt%, especially less than 5 wt%), it is still possible to recycle such structures.

[0139] Those skilled in the art will also recognize that in some embodiments, the use of certain non-polyethylene barrier resins may require the use of a "tie layer" to allow adhesion between the non-polyethylene barrier layer and the remaining polyethylene layer.

[0140] Printing Technology

[0141] As previously noted, in some embodiments, the laminate structures of the present disclosure are printed at the interface of two webs. Suitable processes include the well-known flexographic and rotogravure printing techniques, which typically use nitrocellulose or water-based inks.

[0142] The outer web (described above) forms the exterior of the SUP, while the inner web forms the interior of the SUP. Those skilled in the art typically refer to the outer web as the "printing" web, while the inner web as the "sealant" web.

[0143] Lamination / manufacturing process

[0144] One step in making a laminate structure requires laminating a first web to a second web. There are many commercially available techniques for the lamination step, including the use of liquid glues (which may be solvent-based, solvent-free or water-based), hot melt glues and thermal bonding.

[0145] The SUP packages described above are laminated. The skilled person will appreciate that similar SUPs can be made by coextrusion (using the same materials as the laminated SUP in the same layers). However, the laminated SUP can be printed at the web interface (whereas the coextruded SUP is printed on the surface layer) - therefore, the print quality (and abrasion resistance) of the laminated SUP is superior.

[0146] In one embodiment, the total thickness of inner web B is equal to the thickness of web A. In other embodiments, web B can be from about 2 times the thickness of outer web A to 5 times the thickness of outer web A.

[0147] In one embodiment, the total thickness of the inner web is from 1.3 to 6.0 mils, from 1.8 to 2.6 mils, or such as from 2.0 to 2.5 mils.

[0148] In one embodiment, the first layer thickness is up to 10-20% (of the total thickness of the three layers); the second layer is 40-70%; and the third layer is 10-15% and the fourth layer is 10-20%; the fifth layer is 10-20%. However, those skilled in the art will recognize that further division of the structure can be achieved using devices with up to 9 layers, as more layers can be provided. It should be noted that the first and second layers can be further divided into multiple layers, adding ingredients to modify the properties of the sealant web that are not directly related to the sealing properties. Such properties may include moisture barriers or the need to increase the PCR content of the overall sealant web. The maximum number of total layers will be limited by the number of layers possible in the extrusion unit (called a coextrusion blown film line). In addition, those skilled in the art will recognize that each extrusion unit can, for example, produce nine layers, but can still be used to produce films containing fewer layers.

[0149] In another embodiment, the inner web further comprises a barrier layer, wherein the barrier layer is located between the first B layer and the second B layer. In some embodiments, the barrier layer comprises EVOH, with the further proviso that the total weight of the barrier layer is less than 5 wt%, based on the combined weight of EVOH and the total weight of polyethylene used in the complete structure. In another embodiment, two tie layers are included, such that the first tie layer is located on one side of the barrier layer and the second tie layer is located on the other side of the barrier layer.

[0150] In other embodiments, the thickness of the outer web A may be from about 1 to about 1.4 mils, while the thickness of the inner web may be from about 2 to about 3 mils.

[0151] In another embodiment, the outer web comprises an outer skin layer made of HDPE (e.g., having a thickness of about 0.8 mils) and a LLDPE layer having a thickness of, for example, about 0.4 mils. In this embodiment, the inner layer can be an A / B / C structure, wherein layer A is made of LLDPE (e.g., having a thickness of about 0.4 mils), layer B is a nucleated HDPE (e.g., having a thickness of about 1.5 mils), and layer C is a sealant resin (e.g., VLDPE) having a thickness of, for example, about 0.3 mils.

[0152] Those skilled in the art will recognize that the thicknesses described above can be easily modified to change the physical properties of the SUP. For example, the thickness of the HDPE layer can be increased (if it is desired to produce a stiffer SUP), or the thickness of the LLDPE layer(s) can be increased to improve impact resistance.

[0153] In one embodiment, the total thickness of the laminate structure (i.e., the outer web and the inner web) is from about 3 to about 4 mils. A SUP is then prepared from the laminate structure using techniques and machines known to those skilled in the art. In one embodiment, the laminate structure is sealed using heat sealing to form a SUP. In another embodiment, ultrasonic sealing can be used to form the seal. Example

[0154] The test procedure used to characterize the SUP packaging is briefly described below.

[0155] 1. Melt index: “I 2 ”, measured according to ASTM D1238. [Note: I was measured at 190°C with a 2.16 kg weight. 2 Test.] Test results are reported in units of grams per 10 minutes or decigrams per minute (dg / min).

[0156] 2. Density was determined using the displacement method according to ASTM D792.

[0157] 3. Gloss was measured by ASTM D2457.

[0158] 4. Haze was measured by ASTM D1003.

[0159] Materials List

[0160] The following polyethylenes were used in the examples:

[0161] Resin Type Melt index (g / 10 min) Density (g / cc) Comonomer Web 1. ZN-1 1 0.958 none print 2. ZN-2 0.8 0.934 Hexene Both 3 ZN-3 0.55 0.934 Octene seal 4 DCT-1 1 0.914 Octene Sealant 5. DCT-2 4 0.912 Octene Sealant 6 SSC-1 .nuc 1.2 0.967 none Sealant 7 RXGD 1.5 0.928 Octene Sealant 8 rHDPE-1 0.6 0.962 mix Sealant 9 rHDPE-2 0.6 0.960 mix Sealant

[0162] The prefix ZN indicates that the polyethylene is made using a Ziegler Natta catalyst system. The prefix SSC indicates that the polyethylene is made using a single site catalyst system. The term -(nuc) indicates that the resin contains a nucleating agent (the target site is 1200 parts per million by weight of a commercially available nucleating agent sold by Milliken Chemicals under the trademark HYPERFORM ® 20E sales).

[0163] External web

[0164] Four blown films were prepared as candidates for the outer web of the stand-up pouch. The films were prepared on a conventional blown film line. The total thickness of all films was 2.35 mils (0.059 mm). Films 1.1 and 1.4 were made from only one resin. Films 1.2, 1.3, and 1.5 were multilayer structures comprising HDPE and either MDPE or LLDPE. The machine direction (MD) and transverse direction (TD) stiffness values ​​(expressed in g / cm) for each of these films are shown in Table 1. The thickness of the ZN-1 layer in the multilayer film was 1.15 mils.

[0165] The seal test is accomplished by squeezing two strips of film together (sealant layer to sealant layer) at a set pressure and temperature for a fixed period of time. The temperature is varied to determine the minimum seal temperature (reported as the seal initiation temperature) required to provide a specified / minimum seal strength. The seal temperature is increased until the seal strength begins to decrease (due to melting / failure of the polymer). The results are plotted in a graph.

[0166] Seal strength is determined by an instrument that pulls the seal apart and records the force required to do so. Test methods for determining some seal characteristics are provided below.

[0167] Seal Strength

[0168] The seal strength test is carried out on an instrument designed for this purpose and sold under the trade name INTSTRUME™ 5-head universal tester. The test is generally carried out according to the procedures recommended by the instrument manufacturer.

[0169] Hot glue

[0170] Hot tack is a measure of the ability of a seal to withstand a load before completely cooling; this ability is important for form-fill and seal packaging.

[0171] The test is carried out with an instrument designed for this purpose and sold under the name of the J&B Hot Bond Tester. The test is generally carried out in accordance with the procedures recommended by the instrument manufacturer. The specific conditions are summarized below:

[0172] Sealing pressure: 0.27 N / mm 2

[0173] Sealing time: 0.5 s

[0174] Cooling time: 0.5 s

[0175] Gripper separation speed: 200 mm / sec

[0176] Peel Offset: 5mm

[0177] Sample width: 25 mm

[0178] Sample length: 8 mm

[0179] Table 2

[0180] Printing web film

[0181] structure 1.1 ZN-1 1.2 ZN-1 / SSC-2 1.3 ZN-1 / ZN-2 1.4 ZN-2 1.5 ZN-1 (nuc) / ZN-2

[0182] The (comparative) inner webs having a single sealant layer are shown in Table 3.

[0183] Table 3 (Comparative)

[0184] layer Resin quantity 1 ZN-3 30% 2 SSC-1 .nuc / rHDPE-1 40% 3 DCT-1 30%

[0185] An inner web of the invention having a two layer sealant system (Layers 3 and 4) is shown in Table 4. Layer 4 is the sealant layer (skin layer) and Layer 3 is the "adjacent" layer.

[0186] Table 4

[0187] Internal web structure (invention)

[0188] layer Resin quantity 1 ZN-2 20% 2 rHDPE-1 55% 3 DCT-1 / rLLDPE 10% 4 DCT-1 15%

[0189] Another four-layer film suitable for the inner web is shown in Table 5 (again, layer 4 is the sealant layer, and layer 3 is the "adjacent" layer).

[0190] Table 5

[0191] Internal web structure

[0192] layer Resin quantity 1 ZN-2 20% 2 rHDPE-1 55% 3 DCT-1 / rLLDPE 10% 4 DCT-1 15%

[0193] A five layer film suitable for the inner web is shown in Table 6. Layer 5 is the sealant layer, and layer 4 is the "contact" layer.

[0194] Table 6

[0195] Internal web

[0196] layer Resin quantity 1 ZN-2 5% 2 rLLDPE / rHDPE-2 15% 3 rHDPE-1 55% 4 DCT-1 / rLLDPE 10% 5 DCT-1 15%

[0197] Examples of seven layer films for the inner web are shown in Tables 7 - 9. Layer 7 is the sealant layer and layer 6 is the "contact" layer.

[0198] Table 7

[0199] layer Resin quantity 1 ZN-2 5% 2 rLLDPE / rHDPE-2 15% 3 SSC-1 .nuc 5% 4 rHDPE-1 45% 5 SSC-1 .nuc 5% 6 DCT-1 / rLLDPE 10% 7 DCT-1 15%

[0200] Table 8

[0201] layer Resin quantity 1 ZN-2 5% 2 rLLDPE / rHDPE-2 15% 3 SSC-1 .nuc 7.5% 4 rHDPE-1 40% 5 SSC-1 .nuc 7.5% 6 DCT-1 / rLLDPE 10% 7 DCT-1 15%

[0202] Table 9

[0203] layer Resin quantity 1 ZN-2 5% 2 rLLDPE / rHDPE-2 15% 3 SSC-1 .nuc 7.5% 4 rHDPE-1 40% 5 SSC-1 .nuc 7.5% 6 DCT-1 / rLLDPE / DCT-2 10% 7 DCT-1 15%

[0204] The structures shown in Table 8 have a very good balance of seal and hot tack properties, optical properties, and stiffness. It is possible to improve the optical properties (reduce haze) by replacing SSC-1 with ZN-1, but this is done at the expense of reduced stiffness and MVTR.

[0205] The structures shown in Table 9 have a very good balance of seal and hot tack properties, optical properties, and stiffness. It is possible to improve the optical properties (reduce haze) by replacing SSC-1 with ZN-1, but this is done at the expense of reduced stiffness and MVTR.

[0206] Figure 1 The cold seal curve enhancement is shown in graphical form.

[0207] Table 10

[0208] Sealing properties of sealant webs

[0209] Hot sticking start temperature ℃ Maximum hot adhesive strength (N) Sealing start temperature ℃ Maximum sealing strength (N) Table 3 83.2 7.0 101.9 30.7 Table 4 82.6 6.1 105.6 31.5 Table 8 78.4 8.5 98.0 38.0 Table 9 82.8 7.5 98.6 36.8

[0210] Finished laminate structure

[0211] The finished laminate structure is prepared by laminating the first (outer) web to the second (inner) web.

[0212] Table 10 provides representative data for two finished structures.

[0213] Industrial Applicability

[0214] A stand-up pouch (SUP) made of polyethylene incorporates a sealing structure that improves the manufacture and use of the SUP. The SUP can be used to package a variety of consumer products.

Claims

1. A laminate structure made of a polymer material, the laminate structure comprising: A) Outer web, comprising: A.1) comprising a first A layer of a HDPE composition, and A.2) a second A layer comprising any one or more polyethylenes selected from LLDPE, MDPE and HDPE, wherein the density of the second A layer is lower than that of the first A layer; B) Inner web, comprising: B.1) a first B layer in contact with the outer web, wherein the first B layer comprises either or both of LLDPE and MDPE, B.2) a second B layer comprising recycled polyethylene, which layer is the core layer, and B.3) Sealant structure, including: B.3.1) a sealant skin layer comprising a polyethylene sealant, the polyethylene sealant being a polyethylene copolymer having a density of 0.88 to 0.915 g / cc or a polyethylene homopolymer having a density of 0.91 to 0.93 g / cc; B.3.2) an adjacent layer, the adjacent layer adjacent to the sealant skin layer, the adjacent layer comprising polyethylene having a density a) greater than the density of the polyethylene sealant; and b) less than the density of the core layer contacted by the adjacent layer on a side remote from the sealant skin layer; and in I) the outer web is laminated to the inner web, and II) the HDPE in the first A layer, the polyethylene selected from any one or more of LLDPE, MDPE and HDPE in the second A layer, the LLDPE and / or MDPE in the first B layer, the recycled polyethylene in the second B layer and the polyethylene sealant in the sealant skin layer together form at least 95% by weight of the polymer material used to prepare the laminate structure.

2. The laminate structure of claim 1 wherein the density of the adjacent layers is 0.917-0.921 g / cc and the density of the polyethylene sealant is 0.88-0.915 g / cc.

3. The laminate structure of claim 1 or 2, wherein the polyethylene sealant has a density of 0.900-0.914 g / cc.

4. The laminate structure according to claim 1 or 2, wherein the inner web further comprises an additional layer between B.1 and B.3, the additional layer comprising HDPE containing a nucleating agent or HDPE without a nucleating agent.

5. The laminate structure according to claim 1 or 2, wherein the second B layer comprises HDPE containing a nucleating agent.

6. The structure of claim 1 or 2, wherein the inner web further comprises a barrier layer, wherein the barrier layer is located between the first B layer and the second B layer.

7. The laminate structure of claim 1 or 2, wherein the inner web further comprises at least one layer comprising recycled polyethylene.

8. The laminate structure of claim 1 or 2, wherein the inner web further comprises at least one layer comprising a blend of recycled polyethylene with HDPE, MDPE or LLDPE.

9. The laminate structure of claim 6, wherein the barrier layer comprises EVOH and the total weight of the barrier layer is less than 5 wt% based on the combined weight of the EVOH and the total weight of the polyethylene used in the laminate structure.

10. The laminate structure according to claim 6, wherein a first adhesive layer is disposed on one side of the barrier layer, and a second adhesive layer is disposed on the other side of the barrier layer.

11. A stand up pouch prepared from the laminate structure of any preceding claim.

Citation Information

Patent Citations

  • Stand up pouch

    US20160229157A1

  • Crystalline synthetic resin composition

    US5342868A

  • Modifying agents for polyolefins

    US5981636A

  • Bicyclo[2.2.1]heptane dicarboxylate salts as polyolefin nucleators

    US6465551B1

  • Metal salts of hexahydrophthalic acid as nucleating additives for crystalline thermoplastics

    US6599971B2